Metodologija modeliranja in tvorbe izvorne kode vmesnikov povezljivih vgrajenih naprav - Vinkovič, Sašo (visokošolska dela, 2015)
A methodology that enables a representation of functionalities and features of custom embedded device using a markup language is represented in this doctoral thesis. The design of a functional profile allows for ANSI C source code generation that is suitable for compilation on embedded devices with limited memory and computing power. A new communication protocol named XMC, which is designed for the transmission of messages between an embedded device and a remote system has been developed. Additionally, a new markup language called XMDD has also been developed and is used to describe the functional profile of the embedded device. The main advantage of the XMC communication protocol is its flexibility and independence from the device type. It is suitable for communication with devices that have a curtailed amount of working memory (a few kB) and limited computing power, i.e. 8-bit or 16-bit microcontrollers. Messaging between the embedded device and the remote systems is done without any interference with the basic source code of the embedded device, thus allowing access to all functionalities and features of the connectable embedded device and is based on the functionality dictionary and built-in features of an embedded device. It also maintains a low production price for the embedded device and from the programming point of view, provides a transparent and flexible upgrade of the hardware and software without any redundancy input. The hypotheses were confirmed by the experiment carried out on two embedded devices, namely a refrigerator and built-in oven. The time metrics showed how the length of the XMC communication packet affected the time required for the data transfer between the device and the remote system. For this purpose, the framework that allows for identification and control of household appliances that are designed with the XMC communication protocol was developed. It provides access to all functionalities and features of the connected household appliance that is defined by the appliance's functional profile. The key enabler of the service-oriented architecture is the command interpreter that allows for integration with existing frameworks and definition of new functions and applications by combining the existing functionalities of different appliances. Finally, a comprehensive process of building the software, suitable for connected embedded devices with a curtailed amount of RAM and flash memory has been presented and developed in this dissertation.
Keywords: Avtomatizacija; communication protocol; device identification; Disertacije; embedded systems; functional profile; hišna avtomatizacija; home automation; identifikacija naprave; internet of things; internet stvari; komunikacijski protokoli; pametne naprave; service-oriented architecture; storitveno usmerjena arhitektura; tvorba izvorne kode; vgrajeni sistemi